PROPERTIES OF THE DRUG DORMIKIND - Axmedov Shamshod Jamshidovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. Dormikind – specially created for correction of sleep disorders in infants and young children. . Insufficient or poor sleep quality in children may have a major impact on the whole family. Homeopathy may offer a safe treatment option. In an open, multicenter, randomized, controlled trial the effectiveness of the homeopathic complex medication ZinCyp-3-02 (Dormikind®: cypripedium pubescens D4, magnesium carbonicum D10 and zincum valerianicum D12) was investigated in pediatric sleep disorders Sleep is an important component of our health, and it is especially important for children. Babies are grow, rest and store energy for exploring the world when sleeping. Duration and quality of sleep depends on the age, health and emotional state of the child. According to statistics, sleep disorders in children – a problem of many parents. If a babe does not fall asleep for a long time, has restless sleep during the day, often wakes up at night, then Dormikind can help to deal with the situation.